Analysis of complications after out-of-hospital cardiac arrest of target temperature management - Yun, Cheuh Hsiao; Lin, Chun-Jung; Lin, Kuan-Yu (Journal of the Pakistan Medical Association, 2024)
Objective: To analyse the prevalence of complications related to out-of-hospital cardiac arrest patients achieving target temperature management within 360 minutes compared to those taking more than 360 minutes. Method: The retrospective study was conducted at a medical centre in Taiwan, and comprised data from January 1, 2014, to December 31, 2020. Data was retrieved using the International Classification of Diseases version 10 codes I46.2, I46.8 and I46.9 related to adult patients of either gender presenting to the Emergency Medicine department with out-of-hospital cardiac arrest. Data included gender, age, medical history, body mass index, acute physiology and chronic health evaluation II score, blood glucose levels, electrocardiogram results, and complications occurring within the target temperature management timeframe. Data was divided into group A having patients who achieved target temperature management within 360 minutes, and group B having patients with delayed TTM of more than 360 minutes. Data was analysed using SPSS 22. Results: Of the 127 patients, 76(59%) were males, 51(41%) were males, 47(37%) were aged >75 years, and 13(10.3%) were aged <50 years. Of the total, 65(51.2%) patients were in group A, and 62(48.8%) were in group B. Pneumonia, urinary tract infection, septic shock and gastrointestinal bleeding had lower incidence rates in group A than group B(p<0.05). The odds of death were 2.879 times higher in group B patients than group A (95% confidence interval: 1.908-8.916). Conclusions: Hypothermia treatment should be started as soon as possible to achieve target temperature management within 360 minutes to reduce the risk of complications and mortality. Key Words: Out-of-hospital cardiac arrest, Target temperature management, Risk of death.